2022
DOI: 10.5812/jme-126957
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and Evaluation of Self-directed Learning Activity in Biochemistry for First-Year MBBS Students

Abstract: Background: Self-directed learning (SDL) is an essential teaching-learning method for transforming medical students into lifelong learners. In SDL, learners are responsible for undergoing their learning process and gradually shifting learning control from teacher to themselves. However, First-year MBBS students are in need of receiving training and support to become self-directed learners. Hence, the present study aimed to evaluate the outcomes of adopting SDL alone as well as supplementing SDL with a lecture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…A systematic review published in 2010 reported that self-directed learning (SDL) in health professions education was associated with moderate improvement in the knowledge domain compared with traditional teaching methods [ 13 ]. Thota et al [ 14 ] also supported our finding that lecture cum method which included interactive discussion combination with SDL session improved the post-test score in biochemistry students. We also found the older age was related with lower final exam score.…”
Section: Discussionsupporting
confidence: 83%
“…A systematic review published in 2010 reported that self-directed learning (SDL) in health professions education was associated with moderate improvement in the knowledge domain compared with traditional teaching methods [ 13 ]. Thota et al [ 14 ] also supported our finding that lecture cum method which included interactive discussion combination with SDL session improved the post-test score in biochemistry students. We also found the older age was related with lower final exam score.…”
Section: Discussionsupporting
confidence: 83%